DCF fair value valuation, excessive assetes and hidden inefficiencies - Paweł Mielcarz; Paweł Wnuczak (Contemporary Economics, 2011)
Fair value concept is widely used in DCF (Discounted Cash Flow) business valuation. One of the main principle of fair value concept is full information symmetry between contracting parties. The assumption enforces specific way of FCF (Free Cash Flow) estimation: all areas of inefficiency of valuated companies should be identified and their effect on free cash flow should be eliminated. The projection of free cash flow thus prepared should reflect the optimum operations of the business. The methodological issues of fair value valuation of inefficient companies are not comprehensibly addressed in the financial and accounting literature. There is easily observable gap between fair value theory and valuation practices. Thus this article is an attempt to answer the question about practical issues in fair value valuation of companies which do not apply value based management rules. It is based on literature review, theory examination and short case studies which present proposed solution for practical problems. Methods of identification and assessment of impact of inefficiencies on the fair value of a business are hereinafter presented and supported with arguments.
Keywords: G30; 330; fair value; non-operating assets; valuation of a business